PCK component integration frequency raw data of elementary education teacher educators about biodiversity - Ottogalli, María Emilia (2026)
The present study is part of the qualitative and interpretive paradigm of research, characterized by investigating complex reality from a global approach, where categories and interpretations are built in a process of interaction between data and literature, and it is oriented to interpret the uniqueness of social phenomena in the same context where they occur (Latorre et al., 2005; Patton, 2014). This type of study is based on non-standardized data collection methods in non-probabilistic samples whose results are not intended to be generalized (Hernández Sampieri et al., 2010). Given the exploratory and descriptive nature of our study, we collected data through purposeful sampling of ten elementary teacher educators by the strategy defined as sampling by convenience (Patton, 2014). The selection criterion was based on the willingness of teachers to participate in the study. Context and participants: Teacher training in Argentina takes place both in universities and in non-university higher education institutions (NUHEI) (known as Institutos Superiores de Formación Docente), which differ in terms of curricula and the teaching practices carried out (De Longhi & Rivarosa, 2015). The NUHEIs have state or private management, are the responsibility of the country’s jurisdictions (Ministries of Education of each province) and provide teacher training careers for secondary levels (students between 12 and 17 years of age), elementary (students between 6 and 11 years of age), and initial levels (students of 4 and 5 years of age). According to the curricular standards, the Natural Sciences and its Teaching Method II (NS&TM II) subject has the particularity of having both science education and disciplinary natural sciences contents, organized in three axes. Axis 1 (natural sciences and obstacles in their teaching) includes science education contents (such as previous ideas or alternative conceptions about natural phenomena, constructivist approaches and theories of conceptual change, and assessment in natural sciences), while axes 2 and 3 (axis 2: health education, and axis 3: biodiversity and environment) house disciplinary contents, such as biodiversity and its importance, biodiversity protection, the body and health (Ministry of Education of the province of Córdoba, 2015). In the present study, we have focused on unpacking the pPCK about biodiversity of teachers of NS&TM II who have claimed to address the biodiversity content in axis 3. For this purpose, in 2019, we contacted by telephone or by e-mail teachers who were heads of the subject NS&TM II in NUHEIs offering primary level teaching courses in the city of Córdoba (N = 12). During the first contact, the objective of the interview was explained, the confidentiality of the participants without revealing their names was assured, and it was agreed to share the results once the interviews had been analyzed (Erickson, 2012). We waited one month to give the teachers the opportunity to respond to the emails; after that time, those who did not answer or refused to participate were excluded from the sample and, with those who agreed to collaborate with the research (n = 10), a date was set for an interview. None of the teachers who agreed to be interviewed had previously participated in our research group’s research nor were they currently involved in our teaching, research, or university extension activities. To answer the research question (In what ways are PCK components integrated by ten elementary education teacher educators in biodiversity teaching?), we proceeded to detail the pPCK of each teacher from the description of the components of the pentagon model of PCK (Abell, 2008). For this purpose, between 2019 and 2020, we conducted a semi-structured individual interview with the participating teachers. The interview was composed of the questions of the Content Representation (CoRe) tool (Loughran et al., 2004) and personal data such as age, gender, years of experience in teaching, academic qualifications, etc. The interviews were conducted in person, at the NUHEI where each teacher worked, lasted approximately one hour, and were recorded in audio format with their consent. This allowed us to obtain direct quotations of their experiences, opinions, feelings, and knowledge (Patton, 2014), which were used to unpack teachers’ pPCK on biodiversity. The decision to use the CoRe tool as a guide for the semi-structured interview enables teachers’ knowledge to be accessed and represented (Loughran et al., 2004) and transforms tacit pPCK into explicit pPCK (Alonzo et al., 2019). Although in its original version CoRe is made up of eight questions to be answered based on big ideas for teaching a particular topic (Loughran et al., 2004), in this work, we adapted the methodological strategy following Dueñas et al. (2017), who investigate the PCK of trainee teachers in Colombia for teaching human nutrition. Given that PCK is context and content-specific (Park et al., 2011), and to capture teachers’ knowledge as broadly as possible, we decided to ask teacher educators to answer the questions based on a big idea: the concept of biodiversity. However, as described by Chan (2022), despite the potential of CoRe and its widespread use to document science teachers’ PCK, the tool fails to capture the structure and organization of PCK. Therefore, in the following section, we detail the PCK mapping approach to analyze the integration of biodiversity PCK components from data collected with CoRe. Data analysis: After transcribing the interviews, we performed an axial coding of the identified components of the pentagon model of PCK of Park and Oliver (2008a) (top-down process) and from data emerging categories and sub-categories (bottom-up process) (Patton et al., 2014). This process was conducted with the qualitative data analysis software Atlas.ti® version 7.5.18. The results section presents the categories that correspond to the components of the pentagon model of PCK, the subcategories that emerged from the deductive-inductive analysis, and bullet points for each component of the PCK about biodiversity obtained in the interviews with the teacher educators. The teachers’ pPCK was evaluated using the PCK mapping approach, which was first introduced by Park and Chen (2012). This is an analytic method used to visualize and quantify the interactions of the PCK components (Reynolds & Park, 2021) following these steps: 1) identification of teaching events that explicitly revealed PCK from the coded biodiversity teaching data according to a working definition of PCK, i.e., PCK as an integration of two or more components in the pentagon model of PCK (PCK episode); 2) identification of the PCK components in a particular PCK episode and the connections among the components by using the pentagon model of PCK as an analytic device, which constitutes a PCK map (Park & Suh, 2019). The connections among the components were determined following two assumptions (Park & Chen, 2012): there must be at least one connection between any two of the identified components, and each connection has the same strength or value. Thus, following Suh and Park (2017), for each PCK episode, we elaborated a partial PCK map, then summed up the frequency of the connections between two PCK components and produced a final PCK map for each teacher trainer. The frequency of the connections between two components of PCK was identified in all the episodes and recorded on the pentagon map with a number located above the connection lines. Then, a total count was given to each component connecting to other components of the PCK (Gao et al., 2021) and displayed as a natural number in parentheses, located next to each component. The more connections among PCK components a teacher had, the more integration among PCK components existed (Aydin et al., 2015), with this being an indicator of the integration of the PCK components. Inspired by Park and Chen (2012), we established dashed lines when connection frequencies corresponded to 1 or 2, thinner continuous lines when connection frequencies happened 3 or 4 times, thicker continuous lines for 5 or 6, and continuous lines with the greatest thickness when connection frequencies corresponded to 6 or more connections between two components. In addition, we complement the analysis of the PCK maps with the following relationships between the components of the biodiversity PCK: (a) Number of components integrated in the final PCK map: the number of components of the pentagon model of PCK that are connected in each teacher’s PCK map. The minimum number is 0 and the maximum is 5. b) Total number of integrations in the PCK map: The sum of the total number of connections of each of the five components (numbers in parentheses next to each component) (Aydin et al., 2015). The range varies between 0 and infinity. c) Component(s) with the greatest number (n) of integrations: The component(s) most connected to others in each teacher’s PCK map (Park & Chen, 2012). The range of n varies between 0 and infinity. d) Component(s) with the most diverse integrations (n): PCK component that connects to the largest number (n) of components in the pentagon model of PCK and may or may not coincide with the most integrated component. The minimum number of n is 0 and the maximum is 4. For the validity of the analyzed data, we established instances of triangulation of members of the research team (Aydin et al., 2015). This methodology improves the quality and validity of the results, as different perspectives are provided on the same object of study, thus eliminating single researcher bias (Aguilar & Barroso, 2015). Accordingly, in the present study, each author independently thoroughly content-analyzed these transcriptions to set PCK episodes and identify PCK components (categories) and deductive sub-categories of Table 3. Also, each author inductively delineated provisional subcategories from the transcripts and drew partial and final PCK maps. After that, authors compared their work, discussed the differences, and agreed upon criteria for the next step (e.g., the limits of episodes, the difference between positioning – OTS, and teaching strategy - KISR, the number of connections that are counted to elaborate a partial map when listing elements of a category or subcategory - e.g., evaluation activities, etc.). The authors then reexamined the subset of data, compared their codings, achieving an average agreement of 90.1 % for all PCK components (OTS = 90.1 %; KSC = 92.7 %; KA = 88.9 %; KISR = 90.0 %; KSU = 88.9 %), and resolved the differences through discussion. This procedure and the average interrater reliability match those of Chan and Yung (2018) (> 90 %). Moreover, to increase researcher triangulation, meetings were held with at least two more researchers of the group, in which we discussed the relevance of each code for 4 complete interviews and for fragments of interest of the remaining 6 teacher interviews (approximately, 25 hours of meetings). The fact of being immersed in the data for a long time and jointly practicing coding with additional subsets of data until consistency was reached, helped in providing reliability to the study. Finally, another cycle of researcher triangulation was performed with two external international researchers with experience in the subject, who reviewed and validated the methods of analysis and the interpretations of some general findings with an important level of agreement within the group, and within those with initial internal disagreements. Thus, it was possible to establish the trustworthiness of the study (Aydin et al., 2015).